Next level quotas? Corporate and public support for gender quotas in executive management - Ásta Dís Óladóttir; Thora H. Christiansen; Haukur Freyr Gylfason; Haukur C. Benediktsson; Freyja Vilborg Thorarinsdottir (Administrative Sciences, 2024)
This study provides the first comprehensive examination of gender quota legislation for executive management positions, executive gender quotas (EGQs), in Icelandic listed companies, alongside the general public's attitudes toward such measures. Iceland has been a global leader in gender equality, according to the World Economic Forum, for 15 years, yet progress in achieving gender balance in executive positions remains limited. This research aims to explore how board members in all listed companies in Iceland view EGQ legislation and assess the level of public support for such legislation. Despite the implementation of gender quota legislation for corporate boards, board gender quotas (BGQs), in 2010 aimed at promoting gender balance, significant gender disparities persist at the executive management level. This study reveals distinct attitudes toward EGQs, with men predominantly opposing such legislation and women showing more support, particularly when progress toward gender balance is seen as inadequate. The findings underscore the importance of ongoing dialogue and potential legislative actions to address persistent gender inequalities in leadership positions. This research marks a novel contribution to the discourse on gender quotas in corporate governance, highlighting the need for systemic changes to achieve genuine gender parity in executive management teams. This study presents the first findings on the views of board members and the public on gender quota legislation in executive management positions to close the gender gap in economic participation.
Keywords: 350; board members; corporate governance; executive management; gender inequalities; gender quota